2005
DOI: 10.1590/s1807-59322005000400008
|View full text |Cite
|
Sign up to set email alerts
|

Mitral Valve Annuloplasty With a Bovine Pericardial Strip - 18-Year Results

Abstract: PURPOSE: Prosthetic annuloplasty rings are currently used in mitral reconstruction. Posterior annuloplasty with a bovine pericardial strip is a technique largely used in the Heart Institute of University of São Paulo Medical School. The purpose of the study was to analyze the late results of mitral valve repair with posterior annuloplasty using a bovine pericardial strip. METHODS: Between January 1984 and December 2002, 273 patients underwent mitral valve repair with posterior pericardial annuloplasty in the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The authors found that, on average, there were 16 chordae for the mitral valve combining both valve leaflets. Instead, the literature tends to focus on the use of bovine pericardium in the replacement of valves in humans (Vrandecic and others 1998, Pomerantzeff and others 2005, Li and others 2011). For the pig, again, data were not apparent on the chordae counts for the mitral valve, but the authors have shown that they have slightly more than the sheep and cow, with an average total of 20 chordae.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that, on average, there were 16 chordae for the mitral valve combining both valve leaflets. Instead, the literature tends to focus on the use of bovine pericardium in the replacement of valves in humans (Vrandecic and others 1998, Pomerantzeff and others 2005, Li and others 2011). For the pig, again, data were not apparent on the chordae counts for the mitral valve, but the authors have shown that they have slightly more than the sheep and cow, with an average total of 20 chordae.…”
Section: Discussionmentioning
confidence: 99%
“…21e23 Additionally, ePTFE sutures may have been stretched or pinched by forceps or clips Annuloplasty is performed to prevent dilatation of the annulus by postoperative regurgitation. Previously, autologous pericardium 24 and bovine pericardium 25 or artificial materials such as the Carpentier ring 26 and ePTFE 2,3 have been used for the mitral valve annuloplasty. The Carpentier ring is commonly used in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Although widely used, the rigid rings may have some problems, such as systolic anterior motion in 4% to 10% of cases, causing obstruction of the outflow tract of the left ventricle [16]. In our Service, we have used this technique preferably in the large dilated left ventricle and, in other situations where it is necessary to reduce the annulus, we used a bovine pericardium patch from trigone to trigone, with good late outcomes [17]. A bovine pericardium patch is flexible and does not interfere with the normal anatomy of the mitral annulus, which we now know is not flat and is changed during the different phases of the cardiac cycle.…”
Section: Discussionmentioning
confidence: 99%